THE EFFECTIVENESS OF THE SUPERVISION OF PERPETRATORS OF EFFORT IN PRODUCING QUALITY PRODUCTS AND ITS IMPLICATIONS FOR CONSUMER PROTECTION - Haris, Abd; Miru, Ahmadi; Said, Nurfaidah; Burhamzah, Oky Deviany (Journal of Humanity, 2015)
The purpose of this research was explain how the substance of the law against the perpetrators of the oversight arrangements of effort in producing quality products contained in the legislation in the field of consumer protection, explain how the implementation of surveillance against perpetrators of effort in producing quality products, explain how the form of the application of the sanctions for the perpetrators of the attempt that violates the provisions of the legislation in making products that are not qualified. Research conducted in the framework of this dissertation outlines is of type socio-juridical, because in addition to researching the secondary legal materials in the form of regulations, manual and electronic law library, relevant research results in the field of law of particular problems in the field of consumer protection and other written materials, as well as researching various legal facts about the implementation of surveillance against perpetrators of effort in producing quality products and its implications for consumer protection This is the case, the form of the application sanctions. The results showed that 1). The substance of the law against the perpetrators of the oversight arrangements of effort in producing quality products that are found in a wide range of legislation in the field of consumer protection is basically adequate. 2). surveillance of implementation against the perpetrators of the work done by the three main pillars of supervision: the Government, communities and non-governmental Consumer Protection Agency (LPKSM) is not yet effective due to still having a lot of constraints. 3). The form of the application of the sanctions for the perpetrators of the attempt that violated regulations in making a quality product, it is still better to put forward sanctions administrative compared to criminal sanctions and civil penalties.